Constructing Complex Words in the Dictionary of Ghazi - Ali, Dilbreen (Humanities Journal of University of Zakho, 2024)
Abstract Constructing Complex Words in the Dictionary of Ghazi In linguistics; there are various ways to increase vocabularies in dictionary. One of the ways to increase words is called the complex method. Complex words have not been studied until now in Kurdish language. The study is entitled ``Constructing Complex Words in the Dictionary of Ghazi``. It is a bilingual (Kurdish- Arabic) and (Arabic- Kurdish) dictionary. Throughout this research, the researcher tries to show the constructing complex words that have been used in the Kurdish and Arabic language via certain rules. The research utilizes the qualitative method; this research is of immense significance because it has not been conducted enough in Kurdish language especially in the Bahdini Kurdish dictionary. The purpose of this study is revealing how the rules of the complex words were composed or constructed in the dictionary. In addition to that, the study concentrates on divulging the rate of the rules used in constructing the complex words. In other words, the researcher will confirm how each rule for the constructed complex words have been put into use, and he will also show the percentage of these words. The newness of the title of the research is the chief research problem. Hence the researcher will attempt to display the complex words and their rules as well as their percentage in his research, therefore; the results will be unfolded accordingly. Key words: Words, derivation, percentage, Ghazi dictionary, constructing, complex.